Characterization of Schiff Base Modified MCM-41 Molecular Sieve for Adsorption of Lead Ions from Aqueous Solution - Nkrumah, Kwame; Ferrari, Luca (Journal of Green Energy and Environmental Engineering, 2023)
A new Schiff base modified MCM-41 molecular sieve (N-MCM-41) was synthesized via a post-grafting method using 2-pyridine formaldehyde as the Schiff base ligand to achieve efficient adsorption of lead ions (Pb²⁺) from aqueous solutions. The structure, morphology, surface functional groups, and chemical states of N-MCM-41 were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), and X-ray photoelectron spectroscopy (XPS). The adsorption behavior of N-MCM-41 toward Pb²⁺ in aqueous solution was systematically investigated. The maximum adsorption capacity of this adsorbent for Pb²⁺ reached 101.3 mg/g. The adsorption behavior of Pb²⁺ by N-MCM-41 conformed to the pseudo-second-order kinetic model and the Langmuir isotherm model, indicating that the adsorption process was spontaneous and endothermic. The chelation and coordination between the surface functional groups of N-MCM-41 and Pb²⁺ were identified as the primary mechanism for removing Pb²⁺ from water. After five regeneration cycles, N-MCM-41 retained favorable adsorption performance, demonstrating promising application prospects for the treatment of lead-contaminated water bodies.